Controlling the Uptake of Diarylethene‐Based Cell‐Penetrating Peptides into Cells Using Light. Issue 6 (22nd May 2019) - Schober, Tim; Wehl, Ilona; Afonin, Sergii; Babii, Oleg; Iampolska, Anna; Schepers, Ute; Komarov, Igor V.; Ulrich, Anne S.
Abstract: We report on diarylethene (DAE)‐containing photoswitchable cell‐penetrating peptides (CPPs) capable of photocontrolled cell entry. We demonstrate in vitro that reversible photoisomerization of a DAE fragment in the backbones of non‐cytotoxic cyclic peptides influences their binding to cell membranes and subsequent CPP‐mediated cargo internalization. Benign red light can be used to activate cell entry of our compounds. We suggest that the observed differences in cell uptake of the two photoisomers are due to changes in the molecular flexibility achieved upon DAE photoisomerization. Abstract : Stop and go : The two photoforms of diarylethene‐based cell‐penetrating cyclic peptides show different cellular uptake behaviours triggered by visible light. The flexible isomers, which can be generated by red light, have overall higher activities.